2002
DOI: 10.1086/342412
|View full text |Cite
|
Sign up to set email alerts
|

Immune‐Globulin Prophylaxis of Respiratory Syncytial Virus Infection in Patients Undergoing Stem‐Cell Transplantation

Abstract: Thirty-two patients undergoing allogeneic hematopoietic stem-cell transplantation were given respiratory syncytial virus (RSV) immune globulin (RSVIG) at the time of transplantation and again 3 weeks later. Antibody titers to RSV, human parainfluenza virus 3, measles, and influenza H1N1, H3N2, and B were measured prior to administration of RSVIG and 6 more times over the course of the subsequent 6 weeks. Baseline antiviral titers and increases in antibody after administration of RSVIG were extremely variable f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…More recently, it has been suggested that individuals who receive immunoglobulins containing 140 IU of measles antibodies in the total administered dose will be protected from measles disease [25]; unfortunately, that study did not report the measles immune status before treatment and did not measure either peak or trough levels of measles antibody after infusion. Likewise, in a patient cohort undergoing bone-marrow stem-cell transplantation, measles-antibody titers were measured and were found to be у900 mIU/mL after each of 2 infusions of IGIV and were maintained at or above this level for у21 days after the last infusion [26]; however, these patients had preexisting measles immunity, and the reported mnAb levels after immunoglobulin infusion may not reflect the levels achievable in measles-naive individuals with PIDD.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, it has been suggested that individuals who receive immunoglobulins containing 140 IU of measles antibodies in the total administered dose will be protected from measles disease [25]; unfortunately, that study did not report the measles immune status before treatment and did not measure either peak or trough levels of measles antibody after infusion. Likewise, in a patient cohort undergoing bone-marrow stem-cell transplantation, measles-antibody titers were measured and were found to be у900 mIU/mL after each of 2 infusions of IGIV and were maintained at or above this level for у21 days after the last infusion [26]; however, these patients had preexisting measles immunity, and the reported mnAb levels after immunoglobulin infusion may not reflect the levels achievable in measles-naive individuals with PIDD.…”
Section: Discussionmentioning
confidence: 99%
“…A non-placebo-controlled study showed that RSV immune globulin significantly increased antiviral titers in patients undergoing transplantation but did not show efficacy in preventing RSV infections because of the low incidence of these infections in the study population. 213 The recent discontinuation of RSV immune globulin manufacturing, however, obviates the need for further debate over the use of RSV immune globulin versus IGIV.…”
Section: Transplantation-related Infectionmentioning
confidence: 99%
“…Most regimens include aerosolized ribavirin and passive immunization with either standard IVIG, RSV hyperimmune globulin (RSV-IGIV) or palivizumab. [15][16][17][18] …”
Section: Rsv Infection In Hematopoietic Stem Cell Transplant Recipientsmentioning
confidence: 99%